Validation of physics‐based regional‐scale ground‐motion simulations of the 2008 Mw 7.9 Wenchuan earthquake for engineering applications. (14th July 2022) - Zhang, Fan; Mavroeidis, George P.; Wang, Jingquan; Papageorgiou, Apostolos S.
Abstract: The 2008 M w 7.9 Wenchuan earthquake, one of the largest continental intraplate events instrumentally recorded, struck the central part of Sichuan Province in southwestern China causing great destruction and loss of life but also providing a wealth of seismological data, geodetic measurements, and tectonic observations. The Wenchuan earthquake ruptured two northwest‐dipping imbricate oblique reverse faults along the middle segment of the Longmenshan fault zone—a northeast‐trending thrust belt located at the boundary between the Tibetan Plateau and the Sichuan Basin. In this study, a hybrid approach that combines deterministic modeling at low frequencies with stochastic modeling at high frequencies is used to simulate broadband ground motions at 52 strong‐motion stations and 506 geodetic sites in the vicinity of the causative fault. The low‐frequency components of the synthetic ground motion are simulated using an extended kinematic source model embedded in a layered medium, whereas the high‐frequency components are generated using a stochastic finite‐fault model. The two independently derived ground‐motion components are then combined using matched filtering at a crossover frequency of 0.8 Hz to generate broadband ground‐motion time histories and response spectra. The temporal and spectral characteristics of the synthetic and recorded ground motions at the 52 strong‐motion stations are compared and the effect of soil nonlinearity on the simulated ground motions is investigated through 1‐D nonlinear site response analysis. Finally, the simulated permanent ground displacements at the 506 geodetic sites are evaluated against geodetic observations and the peak amplitudes of the synthetic ground motions at the same locations are compared with predictions of empirical ground‐motion models.